Possible bradykinesia occurrence in lymphocyte division in Parkinson's disease - Inalkac Gemici, Yagmur; Tasci, Irem; Dundar, Muhammed; Ozgen, Nazmi; Gozde Gozukara, Harika; Koc, Ahmet (Ondokuz Mayis Universitesi, 2024)
Lymphocytes have dopamine receptors, and low dopamine levels increase receptor synthesis. Lymphocytes may move slower in Parkinson's, which is characterized by low dopamine levels. We hypothesized that longer telomeres would indicate less lymphocyte division. We investigated whether leukocyte telomere length (LTL) is different in naïve Parkinson’s disease (PD) patients and whether telomere length has clinical significance in determining telomere length in naïve Parkinson's patients. Naïve patients diagnosed with PD were included in this study. 29 naïve PD patients and 15 controls were included in the study. Subgroup analyses were performed according to MMSE and depression scores of PD patients. LTL was measured by RT-qPCR. Differences in LTL between the groups were examined. Clinical and demographic findings and LTL were examined and correlated using appropriate statistical methods. Forty-four participants meeting the inclusion criteria were included in the study. LTL was significantly longer in PD patients than in the control group (p = 0.043) and was positively correlated with clinical worsening of the disease. According to the Analysis of Moment Structures, evaluation total MMSE was 1.82, UPDRS was -1.53, and depression score was -.31 negatively correlated with telomere. LTL was found to be longer in naïve PD patients than in controls. Without other factors that could affect telomere; these findings support the hypothesis that leukocyte division could be slower in PD than the control group at the same age. Additional studies are needed on this subject. Additionally, a longer TL could be a marker for a better clinical course in PD. © 2024 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: biomarkers; cognitive dysfunction; Parkinson's disease; telomer